2022
DOI: 10.3389/fnagi.2022.847561
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3/Caspase-1-Mediated Pyroptosis of Astrocytes Induced by Antipsychotics Is Inhibited by a Histamine H1 Receptor-Selective Agonist

Abstract: Emerging data indicate that antipsychotic treatment causes brain volume loss and astrocyte death, but the mechanisms remain elusive. Pyroptosis, inflammatory cell death characterized by the formation of inflammatory bodies, increased expression of nod-like receptor proteins (NLRPs) such as NLRP3, and activation of caspases and gasdermin D (GSDMD) are largely associated with innate immunity, inflammation, and cell injury/death. However, the main effect of antipsychotics on astrocyte pyroptotic signaling and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…These components are strongly linked to innate immunity, hyperinflammation, and cell damage/expiry. The same study found the main effect of antipsychotic treatments on astrocyte pyroptotic pathways and the molecular processes that could be exerted through inflammasome pathways [89]. In this experiment, 72-h therapy with olanzapine, quetiapine, risperidone, or haloperidol strongly attenuated the astrocytes' viability.…”
Section: Innate Immunitysupporting
confidence: 57%
See 3 more Smart Citations
“…These components are strongly linked to innate immunity, hyperinflammation, and cell damage/expiry. The same study found the main effect of antipsychotic treatments on astrocyte pyroptotic pathways and the molecular processes that could be exerted through inflammasome pathways [89]. In this experiment, 72-h therapy with olanzapine, quetiapine, risperidone, or haloperidol strongly attenuated the astrocytes' viability.…”
Section: Innate Immunitysupporting
confidence: 57%
“…In addition, SCZ patients are often treated with antipsychotic medications that cause brain volume reduction and astrocyte expiry in a process called pyroptosis or proinflammatory cellular expiry [89]. This process involves the formation of inflammatory bodies and enhanced production of complexes such as NLRP3, parallel with the induction of caspases and gasdermin D (GSDMD).…”
Section: Innate Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…The role of other antipsychotics on hypothalamic inflammation has not been elucidated fully. In astrocytes, olanzapine, risperidone, quetiapine, and haloperidol increase IL-1β (He et al, 2022a). In microglia, as has been reviewed, haloperidol and risperidone reduce IL-1β induced by poly (I:C) treatment, but increase IL-6 and TNF-α (Giridharan et al, 2020).…”
Section: The Possible Mechanisms Of Antipsychotic-induced Endoplasmic...mentioning
confidence: 99%